Corticobasal syndrome: neuroimaging and neurophysiological advances. (15th March 2019) - Di Stasio, F.; Suppa, A.; Marsili, L.; Upadhyay, N.; Asci, F.; Bologna, M.; Colosimo, C.; Fabbrini, G.; Pantano, P.; Berardelli, A.
Abstract : Corticobasal degeneration (CBD) is a neurodegenerative condition characterized by 4R tau protein deposition in several brain regions that clinically manifests itself as a heterogeneous atypical parkinsonism typically expressed in adulthood. The prototypical clinical phenotype of CBD is corticobasal syndrome (CBS). Important insights into the pathophysiological mechanisms underlying motor and higher cortical symptoms in CBS have been gained by using advanced neuroimaging and neurophysiological techniques. Structural and functional neuroimaging studies often show asymmetric cortical and subcortical abnormalities, mainly involving perirolandic and parietal regions and basal ganglia structures. Neurophysiological investigations including electroencephalography and somatosensory evoked potentials provide useful information on the origin of myoclonus and on cortical sensory loss. Transcranial magnetic stimulation demonstrates heterogeneous and asymmetric changes in the excitability and plasticity of primary motor cortex and abnormal hemispheric connectivity. Neuroimaging and neurophysiological abnormalities in multiple brain areas reflect asymmetric neurodegeneration, leading to asymmetric motor and higher cortical symptoms in CBS.